Bone health management of Australian breast cancer survivors receiving hormonal therapy. Issue 11 (November 2015) - Roberts, R.; Miller, M.; O'Callaghan, M.; Koczwara, B.
Abstract: Breast cancer survivors are at risk of bone loss due to hormonal treatment. We conducted a case note audit to investigate patterns of care and adherence to guidelines for initial management of risk of bone loss in 42 women receiving hormonal therapy. All those receiving aromatase inhibitors ( n = 14) and 10 on tamoxifen had a bone density assessment. Eleven (26%) women had osteopenia and four (9.5%) osteoporosis. Management was variable and not always aligned with the guidelines.